HUBUNGAN PENGUASAAN KOSAKATA DENGAN KETERAMPILAN MEMBACA PEMAHAMAN PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SEKOLAH DASAR - Sajeeda, Latifa Nawal; Usman, Herlina; Nurhasanah, Nina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the relationship between vocabulary mastery and reading comprehension skills of fifth-grade elementary school students in Indonesian language learning. The study used a quantitative approach with a correlational method. Data collection techniques employed vocabulary mastery tests and reading comprehension tests administered to fifth-grade students. The results showed that the data were normally distributed and the variables had a linear relationship. The Pearson Product Moment test obtained a correlation coefficient value of 0.817 with a significance value of 0.000. The findings indicated a very strong positive relationship between vocabulary mastery and reading comprehension skills. Students with higher vocabulary mastery tended to understand information and interpret reading texts more accurately. The study findings indicated that vocabulary mastery supported students’ reading comprehension skills in Indonesian language learning at the elementary school level.